Phytochemical analysis and in vitro investigation of wound healing, cytotoxicity, and inflammatory response in potentially active extracts of Anogeissus dhofarica - Duaa Abuarqoub, Walid Aburayyan, Luay Rashan, Wael Abu Dayyih, Hisham Y. Al-Matubsi (Journal of Applied Pharmaceutical Science, 2024)
The traditional medicine plant Anogeissus dhofarica is only found in the Jabal Fartak region of Yemen and the Dhofar region of Oman. This plant has been used traditionally for medical purposes to treat wounds, skin tanning, and sores. People use it as an antiseptic, especially women. However, this plant has not been studied in great detail, and there is no scientific proof to back up its traditional uses of it. The goal of this study was to examine the biological properties and phytochemical analysis of various extracts made from A. dhofarica leaves. The powdered leaves of A. dhofarica were extracted using the solvents ethanol (A1), methanol (A3), acetone (A5), and ethyl acetate (A8), yielding concentrations of 3, 0.3, and 0.03 mg/ml, respectively. The total phenolic and flavonoid contents, as well as the active phytochemicals, were determined using standard methods. The proliferation potential and IC50 of human dermal fibroblasts were evaluated. Cytotoxicity, wound healing activity, and the inflammatory response to the extracts were all investigated. Our results revealed that the IC50 values for plant extracts A1, A3, A5, and A8 were 9.799 ± 0.07, 5.83 ± 0.9, 8.8 ± 0.12, and 3.98 ± 0.8 mg/ml, respectively. Moreover, the cytotoxic effect of plant extracts was observed at high concentrations (p
Keywords: Anogeissus dhofarica, total phenol and flavonoid, cytotoxicity, cytokines, inflammatory response, wound healing